Missed foreign body-buccal space - Garg, Manish; Arora, Shilpi; Arora, Shilpi (International Journal of Contemporary Pediatrics, 2022)
Foreign bodies may get embedded in the maxillofacial region as a result of penetrating trauma in the maxillofacial region. The ensuing complications and sequelae of these occult foreign bodies can pose a diagnostic challenge to an oral and maxillofacial surgeon. Diagnosis of these foreign bodies can be achieved by the use of plain radiographs, ultrasonography, computed tomographic scans, and magnetic resonance imaging. Once diagnosed and located, these foreign bodies should be removed for definitive management. I report a case of a persistent sinus of the cheek caused by an occult wood splinter and discuss its diagnosis and clinical management